CERRAHİ TEDAVİ GEREKTİREN MİDE BEZOARLARI - ERSAN, Yılmaz; YAVUZ, Nihat; ÇİÇEK, Yusuf; ERGÜNEY, Sabri; Karataş, Adem; BELLİ, Ahmet; YÜCEYAR, Serdar (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Bezoars are indigestible conglomerates of food, fiber or hair that are found within gastrointestinal tract. Bezoars are usually encountered in patients with altered gastric anatomy and/or function. Especially, persimmon phytobezoar, although an infrequent entity, is not rare in some countries. A number of surgical, endoscopic and pharmacologic treatments have been proposed with variable success. Records of 21 consecutive cases with gastric bezoar undergone surgical treatment at our clinic, between 1982 and 2003, have been reviewed retrospectively. Results.- The age of patients ranged from 15 to 69 years. Mean age of patients was 58.5. Of 21 patients having gastric bezoars, 18 (85.7%) had phytobezoars, 2 (9.5%) had trichobezoars and 1 (4.7%) had a cement bezoar. All patients but one was diagnosed with upper gastrointestinal series and gastroscopical examinations. In one patient who has colonic obstruction due to malignant lesion of transverse colon, gastric phytobezoar was found incidentally during the exploration of the abdomen and was removed through a gastrotomy. 10 (47.6%) patients had a previous gastric surgery. 1 patient associated with chronic calculous cholecystitis and gastric carcinoma underwent cholecystectomy, subtotal distal gastrectomy and Roux-en-Y gastrojejunostomy after complete removal of phytobezoar. Laparoscopic extirpation of phytobezoar was performed in only 1 patient. In others, bezoars were extirpated through a gastrotomy during conventional surgical procedure Recurrence occurred in 1 patient. In this patient, similar procedure was performed. In 1 patient, incisional hernia occurred. Primary repair was performed. Conclusion.- Altogether understanding of bezoars can allow to diagnose the condition at an early stage. Previous ulcer surgery or peptic ulcer plays a major role. Dietary factors (Persimmon or orange) are the main etiologies for formation of bezoars in cases without previous gastric surgery. If conservative treatment (enzymatic dissolution and endoscopik management) is failed, surgical treatment without delay should be performed.